Toward the shell biorefinery: processing crustacean shell waste using hot water and carbonic acid - Yang, Huiying; Gözaydın, Gökalp; Nasaruddin, Ricca Rahman; Har, Jie Ren Gerald; Xi, Chen; Wang, Xiaonan; Yan, Ning (American Chemical Society, 2019)
Biomass fractionation is a prerequisite for almost any biorefinery process. Yet, a cost-effective and environmentally benign approach to separate biomass feedstock into valuable fractions remain a challenge. Herein we introduce a new fractionation method to extract high-value chitin from crustacean shell (e.g., shrimp shell) using hot water for deproteinization and carbonic acid for demineralization (termed as the HOW-CA process). This method features high deproteinization and demineralization efficiencies (>90%), and the whole process is accomplished within hours. The desired final product chitin exhibits a high purity. This work addresses the major problems associated with the current industrial practice including the employment of corrosive reagents, the destructive removal of a useful component, and the generation of a large amount of waste. Economic and life cycle analyses imply that the HOW-CA process is superior to the conventional method, offering both economic and environmental benefits